A New Numerical Algorithm for Two-Point Boundary Value Problems - Lihua Guo; Boying Wu; Dazhi Zhang (Abstract and Applied Analysis)
We present a new numerical algorithm for two-point boundary value problems. We first present the exact solution in the form of series and then prove that the n-term numerical solution converges uniformly to the exact solution. Furthermore, we establish the numerical stability and error analysis. The numerical results show the effectiveness of the proposed algorithm.